Effect of product attributes on customer loyalty in magnum ice cream products - Febrika Rizki Fanora (Institute of Accounting Research and Novation (IARN), 2022)
The purpose of this research is to identify what kind of attributes will be considered by consumers in assessing a product and identifying the influence of product attributes to consumer loyalty of Magnum ice cream. The contribution of consumer loyalty will increase revenue from reorder sales. Product attributes are the important things to gain customer loyalty. This research uses two methods, firstly: exploratory, this method is use to identify product attributes which are important to consumers, secondly: regression, this method is use to determine the effect of each dimension that is formed from the exploratory research on customer loyalty to customer loyalty. Based on the analysis, there is a conclusion that there are five dimensions of ice cream's product attributes, such as the Product Quality, Convenience of Consumption, Comfort of Consumption, Customer Service, and Product Design and Packaging. From the T-test results indicate that the variable Product Quality and Comfort of Consumption have a significant relationship with Consumer Loyalty.